1996
DOI: 10.1128/jcm.34.12.3190-3195.1996
|View full text |Cite
|
Sign up to set email alerts
|

Comparative typing of Pseudomonas aeruginosa by random amplification of polymorphic DNA or pulsed-field gel electrophoresis of DNA macrorestriction fragments

Abstract: Eighty-seven strains of Pseudomonas aeruginosa were typed by random amplification of polymorphic DNA (RAPD) and pulsed-field gel electrophoresis (PFGE) of macrorestriction fragments. Strains were clustered on the basis of interpretative criteria as presented previously for the PFGE analysis. Clusters of strains were also defined on the basis of epidemiological data and subsequently reanalyzed by RAPD. It was found that in an RAPD assay employing the enterobacterial repetitive intergenic consensus sequence ERIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 36 publications
(40 reference statements)
2
35
0
6
Order By: Relevance
“…RAPD analysis of these VRE strains showed no relationship with VRE strains that clustered with PFGE. These phenomena have been described before for VRE and other organisms [7,10,15].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…RAPD analysis of these VRE strains showed no relationship with VRE strains that clustered with PFGE. These phenomena have been described before for VRE and other organisms [7,10,15].…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the two multicentre studies performed to date on Staphylococcus aureus strains show a disappointing degree of reproducibility between centres (see [9] and references therein). Because of these inconsistencies, we became interested in the establishment of interstrain relatedness of vancomycin-resistant enterococci (VRE) by multiple DNA-mediated technologies in order to verify the guidelines brought forward for PFGE [8] while at the same time trying to establish similar frameworks for RAPD typing data [10]. One hundred VRE strains from the UK and The Netherlands were combined in a single collection and for all strains both RAPD and PFGE were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing techniques search the bacterial identities in more depth since the genome of any organism reflects its uniqueness. It has been reported that genetic analysis at the species level gives insight into the variability within a bacterial population and generates evidence on bacterial adaptation to various environmental conditions (Renders et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Randomly amplified polymorphic DNA (RAPD) techniques have been successfully applied to genetic population analysis of a broad range of microorganisms (Olive and Bean 1999) and specifically of Pseudomonas species (Bukanov et al 1994;Elaichouni et al 1994;Haase et al 1995a,b;Renders et al 1996;Hernández et al 1997). It has been demonstrated that RAPD is a universally applicable, rapid and highly discriminating typing method (Elaichouni et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although PFGE is regarded as the most discriminatory method for epidemiological purpose, the results obtained with RAPD-PCR typing have demonstrated good correlation with PFGE (Renders et al 1996). However, preliminary trials of RAPD analysis with several different oligonucleotides primers are necessary to determine the optimal primers and reaction conditions for generation of suitable numbers of DNA bands.…”
Section: Discussionmentioning
confidence: 99%